PERBANDINGAN ANTARA ORDE-2 DAN ORDE TINGGI PADA METODE FINITE DIFFERENCE STAGGERED-GRID DALAM PEMODELAN PENJALARAN GELOMBANG P-SV 2D MENGGUNAKAN GRAPHICS PROCESSING UNIT - , IRCHAN BANI HASYM, Sudarmadji, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A comparison of second order and high order order (4th order, 8th order, 12th order) finite difference staggered-grid method in 2D P-SV elastic wave propagation has been made. A graph comparison of dispersion and accuracy of inter order are made to show stability condition of each order. CUDA C programming language is used to finite difference staggered-grid method to see the process time difference between second order and high order in GPU NVIDIA GeForce GTX 590 (1,5 GB memory) quantitatively. This program has been verified by comparing travel time of direct wave, reflection, refraction, and conversion between synthetic seismogram and analytical line from two layer medium using Snellâs law. The agreement is excellent. Program are applied to one layer medium and complex medium (Marmousi-2). The time process result of one shot with 5,28s duration at Marmousi- 2 model slice with size 4800Ã2400 grid are 1168,72 s (2nd order), 1736,40 s (4th order), 2816,80 s (8th order), dan 3778,67 s (12th order). The difference of seismogram result between second order and high order on two layer model indicated that numerical dispersion has occurred on the waveform. Furthermore, a contrast difference result also seen in Marmousi-2 model seismic data record that seismic data record from second order still has a lot of numerical dispersion effect.